Association of RASSF1A Ala133Ser polymorphism with cancer risk: a updated meta-analysis involving 7362 subjects. (3rd October 2022) - Yin, Guang; Kong, Wencheng; Liu, Xinchun; Zheng, Sixin; Ying, Rongchao; Shan, Yuqiang
Abstract: It has been demonstrated in many studies that the polymorphism of Ras association domain family 1 isoform A (RASSF1A) is related to tumor risk; however, this conclusion remains a controversy. In this study, we systemically retrieved relevant studies in electronic databases such as PUBMED, and EMBASE, and calculated odds ratios (ORs) as well as relevant 95% confidence intervals (CIs). Besides, meta-package in STATA version 12.0 was used. This meta-analysis finally included altogether 12 studies with 16 case-control articles. According to our data, the polymorphism of RASSF1A Ala133Ser was associated with tumor risk (Ser vs. Ala: OR = 1.68, 95% CI = 1.20-2.36; Ala/Ser vs. Ala/Ala:OR = 1.63, 95% CI = 1.16-2.27; Ser/Ser vs. Ala/Ala:OR = 3.06, 95% CI = 1.91-4.89; Recessive model:OR = 2.67, 95% CI = 1.66-4.32; Dominant model: OR =1.72, 95% CI =1.20-2.45). Further, subgroup analyses stratified based on race and cancer type indicated this polymorphism is related to lung cancer(LC) and hepatocellular carcinoma(HCC) susceptibility in Asians.In conclusion, we found that RASSF1A Ala133Ser polymorphism increased LC and HCC risk in Asians, which requires large-scale, delicately-designed researches for verification.